Elevated levels of low molecular weight substances in the red cells of some mammalian species imply unsuspected antioxidant strategies - Davids, Virginia (Department of Clinical Laboratory Sciences, 2014)
An earlier observation by E.H. Harley (supervisor of this thesis) of curious metabolic anomalies in the red cells of black rhinoceros, and in particular a high free tyrosine level, suggested that a range of unusual, but presumeably physiological, processes might be found in mammalian red blood cells. As a follow-up to this, low molecular weight metabolites were examined in a range of mammalian species, using HPLC-based methods to compare levels in red cells with plasma levels. A remarkable interspecies diversity in red cell HPLC profiles was observed, with the unprecedented accumulation of substances including tyrosine, tryptophan, urate, and urate riboside occuring within the red cells of some species. Whereas novel evolutionary adaptations may characterise most of these species-specific variations, the ability of red cells to produce urate is proposed to be an inducible feature common to the red cells of many, or possibly even all, mammalian species. A surprisingly high degree of intraspecies genetic heterogeneity was evident in tyrosine and urate levels within horse, and urate riboside levels within cow red cells. This was in contrast with the greater homogeneity seen in levels of these and other low molecular weight substances in red cells from the other species evaluated. The next phase of investigation addressed the potential function(s) of these soluble substances accumulating within the red cell, particularly relating to a role in antioxidant defense. Using in vitro antioxidant assays such as the 'oxygen radical absorbance' (ORAC) and 'ferrous ion oxidation-xylenol orange' (FOX) assays, results were obtained consistent with a role for these substances as endogenous red cell antioxidants against a variety of reactive species produced by pathophysiological processes in the body. The demonstration that haemoglobin is involved in facilitating some of this activity further substantiates the idea that the red cell may be playing a crucial role in maintaining circulatory redox balance, and hence protecting other tissues from oxidative damage. If indeed such low molecular weight substances contribute to systemic antioxidant activity in some mammalian species, then apart from the intrinsic interest of such unexpected biological phenomena, these findings could pave the way for a plethora of further investigations, geared towards potential clinical applications (eg. as biomarkers or therapeutic approaches) in human and/or veterinary conditions associated with oxidative stress.